Implementasi Teknologi Websocket dalam Pengembangan Sistem Berbagi Lokasi Berbasis Web - Avreghly Barra Al-Ilman; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Location sharing system is a system that allows its users to share their geographic locations to other users. There are at least 80 location sharing service systems now, either in web or native based. The quality of these systems are significantly influenced by their performance that correspond to the selection of the appropriate communication technologies used in communication between client and server. According to the literatures, Websocket technology is the most suitable client-server communication technology for developing a web-based location sharing service system. However, there is no literature which discusses in detail how such technology can be implemented in such system. This research aims to solve such problem by developing a system that utilizes Websocket for client-server interaction to share location. The system was developed in waterfall process model by applying object-oriented development paradigm. The system is built in a client-server construction with Websocket server running on NodeJS runtime environment utilizing the Socket.IO library. The system was tested with three levels of testing: unit testing, integration testing, and system testing. Accuracy test also conducted to check out in what usage condition will the system gave the most accurate location. The white box testing of the unit and integration testing is done using the basis path testing method. The results of this testing indicate that every operation in the system's classes works well. Further, the black-box testing's results of the system testing indicate that all system's requirements have been fulfilled. According to accuracy test, system is recommended to be used in exposure of WiFi connection or GPS access for which both present the best average accuracy value than the other usage condition.